EFEKTIVITAS PENYALURAN ZAKAT PADA PROGRAM BEASISWA PENDIDIKAN TERHADAP PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS - Faris Arkanadhytama Rachman (2023)
The amount of zakat distribution in Indonesia has increased every year. However, the quality of education in Indonesia has not been significantly affected as seen from the dropout rate which has also increased. This research was written with the aim of knowing the level of effectiveness of zakat distribution in the scholarship program at Laznas IZI based on the Sustainable Development Goals. Qualitative method is the method used in this research, and with a case study approach. Data collection techniques by way of observation, interviews, and documentation. Data validation technique with method triangulation and source triangulation. Analysis techniques with data reduction, data presentation, and data verification. The results of this study are that the Laznas IZI Education program is included in the effective category which refers to four categories, namely the accuracy of program targets, program outreach, program objectives, and program monitoring, and the Laznas IZI Education program also contributes to the implementation of achieving the Sustainable Development Goals.